A ratiometric nanosensor based on fluorescent carbon dots for label-free and highly selective recognition of DNA1. Issue 55 (17th June 2015) - Huang, Shan; Wang, Lumin; Zhu, Fawei; Su, Wei; Sheng, Jiarong; Huang, Chusheng; Xiao, Qi
<x xml:space="preserve">Abstract</x> A ratiometric nanosensor based on fluorescent carbon dots for label-free and highly selective recognition of DNA.